Differences in the response of various urogynecology synthetic grafts to infection by Staphylococcus epidermidis: an experimental animal study - Potić, Milan; Ignjatović, Ivan; Damnjanovic, Zoran; Djekić, Petar; Jovanović, Nebojša (Vojnosanitetski pregled, 2025)
Background/Aim. Polypropylene synthetic meshes are used in urogynecology for the primary treatment of stress urinary incontinence. Infection of the graft could influence the outcome of the surgery as well as the adequate tissue reinforcement. The aim of the study was to compare responses to infection in six different synthetic grafts. Methods. The study included six different grafts, with polypropylene as their major component, used for the primary repair of full-thickness abdominal wall defects in male Wistar rats. From a total of 144 Wistar rats, six groups of 24 animals each were created. Each group consisted of 12 animals for noninfected and 12 animals for infected graft testing. In the subgroups for infected graft testing, grafts were inoculated with isolates of Staphylococcus epidermidis. After six weeks, the animals were sacrificed, and groups were compared for inflammatory response, collagen quantification, and abdominal wall reinforcement. The inflammatory response was calculated as the total number of inflammatory cells under a magnification of ×200, including polymorphonuclears, foreign body giant cells, and macrophages. Collagen quantification was determined by colorimetric measurement of hydroxyproline for alkaline hydrolysates. Abdominal wall reinforcement was determined as minimal disintegration load on a standardized shredding device.  In order to detect bacterial biofilm and characterize collagen fibers, scanning electron microscopy (SEM) of fresh samples was performed. Results. Reinforcement of the abdominal wall with a titanium-coated polypropylene graft was most significantly degraded by the infection (p < 0.001). The inflammatory response was the most prominent in the infected multifilament polypropylene graft compared to the low-weight polypropylene graft, titanium-coated graft, and multifilament polypropylene graft with polyglactin (p < 0.01). In terms of collagen deposition, the greatest differences of all grafts were noted between noninfected and infected low- and high-weight monofilament polypropylene grafts (p < 0.01). Using SEM, biofilm formation was detected, and collagen fibers were described as immature. Conclusion. The results of this experimental animal study suggest that infection of synthetic urogynecology grafts results in a significant reduction in tissue reinforcement. In addition, the negative effects of the infection are the most pronounced in multifilament and semi-absorbable multifilament grafts.
Keywords: biofilms; infection; rats; surgical mesh; urinary incontinence, stress